George Washington's war the saga of the American Revolution - Leckie, Robert (Harper Collins, 1992)
In this third volume of brilliant narratives of important events in American history, Robert Leckie brings alive the dramatic story of the American Revolution - just as he caught the drama and excitement of World War II in Delivered from Evil and the Civil War in None Died in Vain. With tremendous narrative pace, remarkable skill at portraying important and fascinating people, a sharp eye for colorful details, and an all-encompassing grasp of historical developments and military action, Leckie traces the course of events from the causes of the break between the American colonies and the British government to the surrender of Lord Cornwallis to George Washington at Yorktown. His descriptions of the many battles - the slaughter and confusion at Concord and Lexington, the Redcoats charging the Continental lines at Bunker Hill, the painful American setbacks at Brandywine and Germantown, and hard-won victories at Saratoga and by John Paul Jones over HMS Serapis at sea - are vivid and exciting. Leckie makes the disputes that caused the conflict - unfair taxes and tariffs, the lack of colonial representation in Parliament - come alive with his descriptions of the Boston Tea Party, the writings of Samuel Adams, and the oratory of Patrick Henry. And his in-depth profiles of the dozens of leading figures on both sides are sprightly and insightful: Washington struggling to keep his army intact despite meager support from the Continental Congress and betrayals by traitors Charles Lee and Benedict Arnold; the ponderous George III in London and his generals in America - Howe, Clinton, Cornwallis, Tarleton, "Gentleman Johnny" Burgoyne, and more; and American commanders like Hamilton, Gates, Greene, Ethan Allen, Morgan, and "Mad Anthony" Wayne. George Washington's War is solid history that reads like superior fiction.
Keywords: Amerikaanse Vrijheidsoorlog; Geschichte; Nordamerikanischer Unabhängigkeitskrieg; Amerikanische Revolution; USA; United States -- History -- Revolution, 1775-1783